Openstage: A Low-Cost Motorized Microscope Stage with Sub-Micron Positioning Accuracy - Campbell, Robert A. A. (Public Library of Science, 2014)
Recent progress in intracellular calcium sensors and other fluorophores has promoted the widespread adoption of functional optical imaging in the life sciences. Home-built multiphoton microscopes are easy to build, highly customizable, and cost effective. For many imaging applications a 3-axis motorized stage is critical, but commercially available motorization hardware (motorized translators, controller boxes, etc) are often very expensive. Furthermore, the firmware on commercial motor controllers cannot easily be altered and is not usually designed with a microscope stage in mind. Here we describe an open-source motorization solution that is simple to construct, yet far cheaper and more customizable than commercial offerings. The cost of the controller and motorization hardware are under $1000. Hardware costs are kept low by replacing linear actuators with high quality stepper motors. Electronics are assembled from commonly available hobby components, which are easy to work with. Here we describe assembly of the system and quantify the positioning accuracy of all three axes. We obtain positioning repeatability of the order of [Image: see text] in X/Y and [Image: see text] in Z. A hand-held control-pad allows the user to direct stage motion precisely over a wide range of speeds ([Image: see text] to [Image: see text]), rapidly store and return to different locations, and execute “jumps” of a fixed size. In addition, the system can be controlled from a PC serial port. Our “OpenStage” controller is sufficiently flexible that it could be used to drive other devices, such as micro-manipulators, with minimal modifications.